The efefctiveness of banana smalholder contract farming on poverty alleviation in Mutasa District - Musakwa, George (Midlands State University, 2020)
This study sought to assess effectiveness of banana smallholder contract farming on poverty alleviation in Mutasa district. The study interrogated the type of contract arrangements between smallholders and the contractor in Mutasa district, the impact of banana contract farming on poverty alleviation, the challenges faced by smallholder farmers through contract farming in attempting to reduce household poverty in the area under study and the sustainability of contract farming in Mutasa district. The study was a mixed research and it employs both quantitative and qualitative research methods. The researcher has used the following data collection tools, questionnaire, interview and focus group discussion. The researcher found out that the type of banana contract was the all-in-one which provides transport, technical advice, market and inputs to the contracted farmers. Banana contract farming has yielded positive results in terms of improving the lifestyle of the smallholder farmers in Mutasa district. The study revealed that contracted smallholder farmers’ households have managed to be food secure as they were able to purchase basic foods with the money they got after selling their bananas. Household income among the contracted farmers have been improved positively as many contracted farmers have managed to invest in productive asserts like livestock, grinding mill, scotch carts among others and this contributed much to poverty eradication. However, there were some challenges faced by the small holder farmers like high transport cost from there field to the collection point, poor road network from the community to the main tarred road, unstable prices of bananas. The researcher also recommended that the government should be active in smallholder contract farming to effect measurement of poverty alleviation. Government should improve road networks, enforce good agricultural policies that protect both the contractor and contracted smallholder farmers and monitoring the implementation of contract farming.